Transmit scheme for GLSFBC-CDMA-OFDMA system - Jin-long ZHAN; Jian-jun LU; Guang-yue LU (Tongxin xuebao)
A novel GLSFBC (group layered SFBC)-CDMA-OFDMA multiple antenna transmit scheme was proposed over frequency-selective fading channels.The proposed scheme is based on a three-level design of cascade codes:the first level(based on OFDMA)deals with multi-user interference and frequency-selective fading,the second level(based on CDMA) handles group interference and obtains frequency diversity gain,and the third level (based on GLSFBC) results in space diversity and multiplexing gain.At the receiver,the proposed approach only needs one antenna to suppress both multi-user interference and SFBC group interference,so it makes the receiver construction simple.Both theory analysis and computer simulation prove the validity of the novel technique.